2023
DOI: 10.3390/su15129811
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Impacts of Land Use and Land Cover (LULC) Change on Stream Flow and Runoff in Rur Basin, Germany

Abstract: Understanding the impact of land use/land cover (LULC) change on hydrology is the key to sustainable water resource management. In this study, we used the Soil and Water Assessment Tool (SWAT) to evaluate the impact of LULC change on the runoff in the Rur basin, Germany. The SWAT model was calibrated against the observed data of stream flow and runoff at three sites (Stah, Linnich, and Monschau) between 2000 and 2010 and validated between 2011 and 2015. The performance of the hydrological model was assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…In general, human activities characterized by urban development, agricultural activities and deforestation systematically leads to LULC changes, which then results in environmental changes that impacts on the earth-atmosphere interactions and sustainable development [107]. The increasing population and related human activities coupled with climate change have progressively led to the decline in per capita water availability [108]. The decline is estimated to have a 6-fold increase over the past century and is predicted to rise annually at a rate of 1% [109].…”
Section: Insights Into Lulc Change and Land-water Sustainabilitymentioning
confidence: 99%
“…In general, human activities characterized by urban development, agricultural activities and deforestation systematically leads to LULC changes, which then results in environmental changes that impacts on the earth-atmosphere interactions and sustainable development [107]. The increasing population and related human activities coupled with climate change have progressively led to the decline in per capita water availability [108]. The decline is estimated to have a 6-fold increase over the past century and is predicted to rise annually at a rate of 1% [109].…”
Section: Insights Into Lulc Change and Land-water Sustainabilitymentioning
confidence: 99%
“…SWAT presented a greater potential in the management of the risks of extreme hydrological events [14,15]. The SWAT model comprehensively considers the hydrological process differences of the underlying surface of the basin and found that climate change and LUCC have impacts on hydrological processes such as evapotranspiration (ET), runoff, infiltration, and hydrological response [16]. Hence, the comparison of hydrological processes changes under different climate changes and LUCC scenarios using SWAT models is important for understanding the response of hydrological processes to changing environments.…”
Section: Introductionmentioning
confidence: 99%